Analisis Perbandingan Rasio Keuangan PT Unilever Indonesia Tbk dengan PT Kino Indonesia Tbk Sebelum dan Sesudah Pandemi Covid-19 Periode 2018 Sampai 2021 - Hendra Jati; Sri Hermuningsih (Universitas Batanghari, 2023)
The Covid-19 pandemic has had an impact on various sectors in Indonesia. As a result of the pandemic that occurred, it affected the company's financial performance. Financial performance is the ability of an organization or company to achieve the expected financial targets. Companies should continue to strive in managing their resources efficiently and effectively, so that the company can achieve its goals. Financial statement analysis can be done using financial ratios. Financial ratios that are often used include Liquidity Ratios, Solvency Ratios, Profitability Ratios, Activity Ratios, and Inventory Turnover Ratios. The purpose of this study was to determine whether the financial ratios of the companies PT Unilever Indonesia Tbk and PT Kino Indonesia Tbk were in good condition and which financial ratios were better between the two companies before and after the Covid-19 pandemic. From the results of the study, it can be concluded that the financial ratios of PT Kino Indonesia Tbk are better than PT Unilever Indonesia Tbk during the period 2018 to 2021 during conditions before and after the Covid-19 pandemic.